Mobility as a Service: A new ambition for public transport authorities - Yves Crozet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper examines the relationship between traditional public transport and innovative mobility solutions such as Mobility as a Service (MaaS). It looks at how MaaS could change the role of public transport authorities from providing transport services to facilitating mobility, and considers how their remit and capabilities should evolve to better promote seamless multimodal transport.
Keywords: 330; Öffentlicher Verkehr; Mobilität; Dienstleistungsqualität; Strukturwandel